Evaluation of lawn color and chlorophyll concentration using hyperspectral index. Issue 1 (December 2020) - Zhang, Wen; Chen, Gong; Wu, Hongzhi; Xie, Caiyun; Wang, Zhiwei; Song, Xuelian; Wang, Puchang; Ruan, Xirui; Ding, Leilei; Zhang, Yujun; Liu, Jiajia
Abstract: A study was carried out at a subtropical zone of southern west China to test if hyperspectral methods could be used to measure turf canopy chlorophyll concentration, and to analyse correlation between green normalized difference vegetation index (GNDVI) values. Turf chlorophyll concentration, canopy hyperspectral reflectance, and visual rating were measured. The results showed that canopy hyperspectral reflectance value was more sensitive to the turfgrass chlorophyll concentration difference than visual rating both among turfgrass species. Visual rating value and hyperspectral index were both highly correlated with canopy chlorophyll concentration. Regression analysis indicated a strong linear correlation between GNDV and visual rating value. Hyperspectral technique can provide an improved method to evaluate turfgrass chlorophyll concentration and to quantify turfgrass color.